Fabrication of 3D freeform porous tubular constructs with mechanical flexibility mimicking that of soft vascular tissue. (March 2019) - Lee, Ji Eun; Park, Seong Je; Yoon, Yeji; Son, Yong; Park, Suk-Hee
Abstract: Three-dimensional (3D) printing, with its capability for producing arbitrary shapes, has been extensively studied for tissue engineering applications. However, clinical applications, especially for soft tissues, have been limited due to mechanical mismatch between the 3D-printed artificial tissues and the native tissues. Here, we suggest an integrative method of 3D printing, dip coating, and salt leaching for the fabrication of soft 3D freeform porous tubes, which are expected to be applied to the engineering of vascular tissues. Owing to their porous morphology and controlled wall thickness, the processed tubular constructs had flexible properties comparable to those of native soft tissues with a modulus range of several MPa. When thermoplastic polyurethane (TPU) was used as the dip-coating material, the porous tube exhibited a low tensile modulus from 1.47 to 2.47 MPa and a high elongation limit of over 400%. These flexible properties, which were clearly differentiated from the stiffness of 3D-printed samples with moduli of tens or hundreds of MPa, were confirmed to mimic the mechanical properties of native tissues. Furthermore, by varying the material composition in the dip-coating process, the flexibility of the tube could be modulated when stiffer polycaprolactone (PCL) layers were combined. In addition, such a combination using biocompatible materials could be expected to provide safer interaction at surgical interfaces. Synergistically with the mechanical flexibility, since the proposed method was based on a 3D-printed template, the resulting construct would have extensive applicability in patient-specific tissue engineering.